Development of Conventional Refrigeration Control System Learning Media, Automatically Cooling and Defrost System - I Wayan Dikse Pancane (PT FORMOSA CENDEKIA GLOBAL, 2023)
Development of Learning Media aims to design a Conventional Automatic Refrigeration Control System Design for Refrigeration and Defrosting Systems so that it can assist the learning process in Class XI Refrigeration Engineering. This research is a type of R&D level 3. This study used a questionnaire as an instrument to collect data from content experts, media experts, and students. The results of the material expert trial obtained a percentage value of 93.33%, with very decent qualifications, the media expert trial results obtained a percentage of 97.64%, with very decent qualifications, the small group trial results obtained a percentage value of 90.25% , with very decent qualifications, the results of the large group trial data obtained a percentage of 90.04%, qualifications Based on the research results, the media is feasible and good to be used as a learning medium in the subject of Refrigeration Systems and Installation in class XI TP majoring in Electrical Engineering, package refrigeration and air conditioning engineering expertise at SMK Negeri 1 Denpasar